Cytoreductive surgery with hyperthermic intraperitoneal chemotherapy for peritoneal malignancy: preliminary results of a multi-disciplinary teamwork model in Asia. (3rd April 2018) - Wang, Ting-Yao; Chen, Chao-Yu; Lu, Chang-Hsien; Chen, Min-Chi; Lee, Li-Wen; Huang, Tzu-Hao; Hsieh, Meng-Chiao; Chen, Chih-Jung; Yu, Chung-Ming; Chuang, Huei-Chieh; Liao, Tzu-Ting; Tseng, Chih-Wen; et al.
Abstract: Background: Cytoreductive surgery with hyperthermic intraperitoneal chemotherapy (CRS/HIPEC) is an emerging surgical procedure for peritoneal carcinomatosis (PC). CRS/HIPEC is a complicated treatment that requires multi-disciplinary teamwork (MDT), which may be lacking when establishing a CRS/HIPEC programme. Herein, we report our preliminary treatment outcomes with the early implementation of an MDT model for CRS/HIPEC. Methods: From April 2015 to December 2016, 45 patients with a diagnosis of PC who received CRS/HIPEC were reviewed retrospectively in a single institution in Taiwan. Results: Among the 45 patients, CRS was mainly performed by laparotomy ( n  = 42), and only three patients with limited PC underwent laparoscopic CRS. The first 13 patients received treatment before the MDT had been established (group 1), and the other 32 patients were treated after the MDT had been established (group 2). The highest peri-HIPEC body temperature in group 2 was significantly lower than that in group 1 (36.8 °C vs. 37.5 °C, p  < 0.001). Overall, eight patients experienced major complications. The trend of a lower major complication rate was observed after the MDT model had been implemented (30.7% in group 1 vs. 12.4% in group 2, p  = 0.202). Pre-CRS/HIPEC abdominal pain significantly increased the risk of post-operative major complications ( p  = 0.017). Conclusions: Our experience suggests that the early implementation of an MDT model when establishing a CRS/HIPEC programme at a single institution may result in a higher complete cytoreduction rate and lower major complication rate, and also shorten the learning curve of this complicated procedure.